2002
DOI: 10.1063/1.1467973
|View full text |Cite
|
Sign up to set email alerts
|

Nanopatterning of alkyl monolayers covalently bound to Si(111) with an atomic force microscope

Abstract: Alkyl monolayers covalently bound to silicon were prepared through the reaction between 1-alkene molecules and hydrogen-terminated Si. The surfaces were anodized in nanometer scale with a contact-mode atomic force microscope (AFM) by applying positive bias voltage to the surface with respect to a conducting cantilever under ambient conditions. Following the anodization, patterned areas were selectively modified by chemical etching and coating with different molecules. The alkyl monolayers showed high resistanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
52
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(54 citation statements)
references
References 23 publications
2
52
0
Order By: Relevance
“…By using a terminally functionalized alkoxysilane, such as 3-aminopropyl (trimethoxysilane), these nanopatterned self-assembling molecules can act as a template for binding more complex nanostructures, including nanoparticles (Sugimura and Nakagiri, 1997b), proteins (Sugimura and Nakagiri, 1997a), and carbon nanotubes . In a similar study Ara et al (2002) demonstrated that AFM field-induced oxide patterns on an alkyl terminated silicon surface could be selectively etched in ammonium fluoride to remove the oxide and then act as a template for selective binding of terminal alkenes by a direct silicon-carbon covalent bond. In Fig.…”
Section: Electrochemical Lithographymentioning
confidence: 95%
“…By using a terminally functionalized alkoxysilane, such as 3-aminopropyl (trimethoxysilane), these nanopatterned self-assembling molecules can act as a template for binding more complex nanostructures, including nanoparticles (Sugimura and Nakagiri, 1997b), proteins (Sugimura and Nakagiri, 1997a), and carbon nanotubes . In a similar study Ara et al (2002) demonstrated that AFM field-induced oxide patterns on an alkyl terminated silicon surface could be selectively etched in ammonium fluoride to remove the oxide and then act as a template for selective binding of terminal alkenes by a direct silicon-carbon covalent bond. In Fig.…”
Section: Electrochemical Lithographymentioning
confidence: 95%
“…Many research works for the fabrication of site-controlled nano-structures by artificial techniques have been reported by using electron-beam lithograph [11], scanning tunneling microscope (STM) tip-assisted patterning [12], and atomic force microscope (AFM) tip-induced oxide patterning [13][14][15][16][17]. A number of works demonstrated that an AFM could be used for the oxidation on semiconductors and metal films [13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Nano-hole structures were introduced by depositing a thin GaAs layer on STM tipassisted patterning on GaAs (0 0 1) substrate [12], electron-beam lithography combined with Cl 2 gas etching on GaAs [11], and locally strain-enhanced etching of a GaAs cap layer grown on an InAs QD layer [19]. Nano-trench structures were also fabricated by AFM tip-induced oxidation based on NH 4 F etching on modified Si (1 1 1) [18] and direct patterning on GaAs (1 0 0) surface by AFM [20]. In addition, to realize the site-controlled nano-structures based on the migration control of adatoms, the atomically flat surface is also required after the formation of nano-holes and trenches because the atomic migration on surface can be seriously affected by surface roughness.…”
Section: Introductionmentioning
confidence: 99%
“…The binding of diverse silanes to silicon oxide surfaces has been the subject of several investigations [2224]. Though a previous study demonstrated the general feasibility to bind silane molecules to LAO nanostructures, there was strong evidence for only a partial coverage of the structure and no complete monolayer formation [25]. …”
Section: Introductionmentioning
confidence: 99%